ADENOSINE DEAMINASE ACTIVITY IN SYNOVIAL FLUID AT ARTHRITIS (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
It was found that the levels of Adenosine deaminase activity in joint effusions of patients with rheumatoid arthritis and osteoarthritis differ significantly (p < 0.0001). To differentiate the arthritis of these two etiologies, the cutoff value of the enzyme activity in synovial fluid was evaluated as 12 IU/L with sensitivity 0.96, specificity 0.89 and diagnosis efficiency 0.93. Based on this observation, we can offer using in clinics of Armenia the Adenosine deaminase activity in synovial fluid for quick diagnosis of rheumatoid arthritis as a sensitive, specific, low-cost and technically convenient test.
Keywords: adenosine deaminase; ADA-test; differentiation of arthritis; rheumatoid arthritis; osteoarthritis; synovial fluid